2021
DOI: 10.1007/s00134-021-06487-y
|View full text |Cite
|
Sign up to set email alerts
|

No clinically relevant removal of meropenem by cytokine adsorber CytoSorb® in critically ill patients with sepsis or septic shock

Abstract: share senior authorship.The members of the CytoMero collaboration team are listed in the Acknowledgements section of the manuscript.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…These drugs are presented in Table 1 and include anidulafungin, cefepime, ceftriaxone, ciprofloxacin, clarithromycin, clindamycin, flucloxacillin, ganciclovir, meropenem, metronidazole, and piperacillin. A recently published investigation confirmed the absence of clinically relevant removal of meropenem by CytoSorb in patients with sepsis or septic shock (28).…”
Section: Considerations For the Interpretation Of Available Pharmacok...mentioning
confidence: 84%
“…These drugs are presented in Table 1 and include anidulafungin, cefepime, ceftriaxone, ciprofloxacin, clarithromycin, clindamycin, flucloxacillin, ganciclovir, meropenem, metronidazole, and piperacillin. A recently published investigation confirmed the absence of clinically relevant removal of meropenem by CytoSorb in patients with sepsis or septic shock (28).…”
Section: Considerations For the Interpretation Of Available Pharmacok...mentioning
confidence: 84%
“…An in vitro study suggested the need for administration of an additional antibiotic dose within the first few hours of CytoSorb® treatment and for early therapeutic drug monitoring since all antimicrobial drugs tested were adsorbed by the cartridge in relevant amounts 49 . However, reliable quantitative clinical data is needed to confirm these findings 54 . Another in vitro study found that remdesivir and its main active metabolite were eliminated by CytoSorb® 52 .…”
Section: Discussionmentioning
confidence: 99%
“…49 However, reliable quantitative clinical data is needed to confirm these findings. 54 Another in vitro study found that remdesivir and its main active metabolite were eliminated by CytoSorb ® . 52 Hence, without proper monitoring, some drugs may reach subtherapeutic levels and thus negatively impact patient outcome.…”
Section: Relationship To Previous Studiesmentioning
confidence: 99%
“…As significant losses of amino acids and several micronutrients, such as vitamins B1 and C, copper and selenium can occur, careful monitoring in prolonged KRT should be considered 156 . Importantly, discrepancies exist in the observed and predicted removal of antimicrobials with haemoadsorption in critically ill patients [157][158][159][160][161][162][163] . In patients undergoing continuous KRT, anti microbial clearance depends on the effluent fluid rate and therapeutic drug monitoring should therefore be considered where available 157 .…”
Section: Delivery and Monitoring Of Extracorporeal Blood Purification...mentioning
confidence: 99%